Headspace Solid-Phase Microextraction Analysis of Volatile Components in Peanut Oil - Yang, Kai-Min; Chao, Louis Kuoping; Wu, Chin-Sheng; Ye, Zih-Sian; Chen, Hsin-Chun (Molecules (Basel, Switzerland), 2021)
Peanut oil is favored by consumers due to its rich nutritional value and unique flavor. This study used headspace solid-phase microextraction (HS-SPME) combined with gas chromatography (GC) and gas chromatography–mass spectrometry (GC-MS) to examine the differences in the peanut oil aroma on the basis of variety, roasting temperatures, and pressing components. The results revealed that the optimal conditions for extracting peanut oil were achieved through the use of 50/30 μm DVB/CAR/PDMS fibers at 60 °C for 50 min. The primary compounds present in peanut oil were pyrazines. When peanuts were roasted, the temperature raised from 120 °C to 140 °C and the content of aldehydes in peanut oil increased; however, the content of aldehydes in No. 9 oil at 160 °C decreased. The components of peanut shell oil varied depending on the peanut variety. The most marked difference was observed in terms of the main compound at the two roasting temperatures. This compound was a pyrazine, and the content increased with the roasting temperature in hekei oils. When the roasting temperature was lower, No. 9 oil contained more fatty acid oxidation products such as hexanal, heptanal, and nonanal. When the roasting temperature increased, No. 9 oil contained more furfural and 5-methylfurfural. Heren oil was easier to oxidize and produced nonanal that possessed a fatty aroma.